2016
DOI: 10.1007/s12015-016-9648-6
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Maternal-Effect Genes in Mammalian Development: Are Mammalian Embryos Really an Exception?

Abstract: The essential contribution of multiple maternal factors to early mammalian development is rapidly altering the view that mammals have a unique pattern of development compared to other species. Currently, over 60 maternal-effect mutations have been described in mammalian systems, including critical determinants of pluripotency. This data, combined with the evidence for lineage bias and differential gene expression in early blastomeres, strongly suggests that mammalian development is to some extent mosaic from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 148 publications
0
37
0
Order By: Relevance
“…Many maternal effects are readily apparent through early, direct negative consequences during embryo life when they are disrupted. Across diverse species such effects encompass mutations that compromise essential early oocyte functions such as meiosis or yolk deposition, localized ooplasmic determinants in some species, and chromatin regulators and other factors that are required for genome programming and activation (Condic, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many maternal effects are readily apparent through early, direct negative consequences during embryo life when they are disrupted. Across diverse species such effects encompass mutations that compromise essential early oocyte functions such as meiosis or yolk deposition, localized ooplasmic determinants in some species, and chromatin regulators and other factors that are required for genome programming and activation (Condic, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many maternal effect genes in mammals have been described that impact key early processes, which, when disrupted, are associated with early embryo demise (Condic, 2016; Lu, Gao, Qin, & Li, 2017). Although the study of such mutations is valuable for understanding essential early developmental processes, its relevance to understanding long‐term phenotypic effects is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The low transcriptional activity before zygotic genome activation indicates that maternal-effect genes play essential roles in early embryonic development (Li et al, 2013(Li et al, , 2010. Since the initial identification of the maternal-effect genes Nlrp5 (also known as Mater) and Hsf1 (Christians et al, 2000;Tong et al, 2000), dozens of maternal-effect genes have been reported (Condic, 2016;Li et al, 2010). Yet, how the maternal-effect genes regulate early embryonic development remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the application of newly developed techniques to investigate both preceding and subsequent stages, including gametogenesis − with particular focus on oocyte maternal factors (Li et al . 2010, Condic 2016), as well as preimplantation, peri-implantation and postimplantation embryos (Deglincerti et al . 2016, Shahbazi et al .…”
Section: Discussionmentioning
confidence: 99%